Primary hyperparathyroidism with severe bone disease: osteitis fibrosa cystica vs. fibrous dysplasia. case report and review of the literature - Leitão, MJ (1999)
Primary hyperparathyroidism _HPT. is associated with generalized skeletal changes, its full-blown osseous manifestations known as osteitis fibrosa cystica. Fibrous dysplasia _FD., a benign bone disorder, is differentiated from generalized fibrocystic disease caused by hyperparathyroidism. The classic triad of McCune–Albright syndrome includes polyostotic FD, patchy skin pigmentation, and sexual precocity. Other associated endocrinopathies are hyperthyroidism, Cushing’s syndrome, acromegaly, and HPT. We describe a patient with severe generalized and focal bone lesions and sexual precocity. HPT was diagnosed and treated with persistence of cystic bone lesions. The similarities between HPT and FD are discussed, focusing on a possible genetically determined mechanism to explain the relationship between them.